2018
DOI: 10.1177/2325967118816293
|View full text |Cite
|
Sign up to set email alerts
|

Resident Involvement in Shoulder Arthroscopy Is Not Associated With Short-term Risk to Patients

Abstract: Background:Shoulder arthroscopy is a commonly performed, critical component of orthopaedic residency training. However, it is unclear whether there are additional risks to patients in cases associated with resident involvement.Purpose:To compare shoulder arthroscopy cases with and without resident involvement via a large, prospectively maintained national surgical registry to characterize perioperative risks.Study Design:Cohort study; Level of evidence, 3.Methods:The prospectively maintained American College o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
(37 reference statements)
1
25
1
Order By: Relevance
“…Using the NSQIP database, Basques et al 23 investigated resident involvement in shoulder arthroscopy. They identified a 1.09% overall complication rate with resident involvement not being associated with complications, adverse events, or 30-day readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Using the NSQIP database, Basques et al 23 investigated resident involvement in shoulder arthroscopy. They identified a 1.09% overall complication rate with resident involvement not being associated with complications, adverse events, or 30-day readmission.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 Previous studies have investigated the impact of resident involvement on adverse outcomes and readmissions after spine surgery, total joint arthroplasty, and shoulder arthroscopy. 2,5,7,9,13,14 The purpose of the current study was to use a large national data set to compare operative time, adverse events, and readmission for arthroscopic knee surgery cases with and without resident involvement. Our hypothesis was that operative time, adverse events, and readmissions would not significantly differ between arthroscopic knee surgery cases with and without a resident involved in the performance of the procedure.…”
mentioning
confidence: 99%
“… 3 , 15 Previous studies have investigated the impact of resident involvement on adverse outcomes and readmissions after spine surgery, total joint arthroplasty, and shoulder arthroscopy. 2 , 5 , 7 , 9 , 13 , 14 …”
mentioning
confidence: 99%
“…Although a variety of studies have previously used the American College of Surgeons NSQIP database to examine the impact of resident involvement in orthopaedics, most focused on complication rates and safety, 20,24,[44][45][46][47][48][49] and few studies have examined procedures common in sports medicine. 27,50,51 Basques et al 27 examined the role of resident involvement in shoulder arthroscopy, reporting no change in operative time between attending-only cases and resident-involved cases. However, the findings have limited generalizability to our study because of differences in the date range of data used, variable selection of CPT codes, and no stratification of operative time findings by CPT code.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies have reported a lower or equal risk of perioperative complications and associations with care for more medically complex patients, others have reported longer operating times, greater morbidity, and longer hospital stay durations. 20,[23][24][25][26] The impact of resident involvement in academic sports medicine is particularly poorly studied, with few studies examining complications, safety, or operative time 27,28 and only a single study using this data to estimate the cost of resident involvement in rotator cuff surgery. 29 For the aforementioned reasons, the purpose of this study is to quantify the cost of resident involvement in academic sports medicine by examining differences in operative time, relative value units (RVUs) per case, and RVUs per hour between attending-only cases and cases with resident involvement.…”
mentioning
confidence: 99%